2010
DOI: 10.1386/jammr.3.1-2.121_1
|View full text |Cite
|
Sign up to set email alerts
|

Credibility of Palestinian media as a source of information for opinion leaders

Abstract: The main concern of this research is the credibility of Palestinian media amongst opinion leaders. The study surveyed 860 opinion leaders, (442) in the West Bank and (418) in Gaza, using purposive sample techniques. To assess credibility, opinion leaders were asked to answer according to the credibility scale developed by Gaziano and McGrath. The findings show that 35.6% of the opinion leaders considered the 'Al-Jazeera' satellite TV station to be the most credible media source. Of the sample, 6.9% said the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…However, here it is important to note the nature of the event. Aqtash (2010) found that in the Middle East, when people feel that traditional media are biased, they view it as less credible and hence seek more informed opinions from a variety of sources, particularly social media. Yardi and boyd (2010) examined Twitter posts on controversial topics and found that replies to and from like-minded individuals increased group identification and communication with different minded tweeters reinforced both in-group and out-group affiliation.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…However, here it is important to note the nature of the event. Aqtash (2010) found that in the Middle East, when people feel that traditional media are biased, they view it as less credible and hence seek more informed opinions from a variety of sources, particularly social media. Yardi and boyd (2010) examined Twitter posts on controversial topics and found that replies to and from like-minded individuals increased group identification and communication with different minded tweeters reinforced both in-group and out-group affiliation.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…In lieu of this, the likes of Wieviorka (), Wilkinson (), and Surette, Hansen, and Noble () have explored the “symbiotic relationship” (Wilkinson, , p. 54) between the media and terrorists. Others like Aqtash (), studying the credibility of Palestinian media sources, have condemned the Hamas/Fatah‐run media landscape for being partisan, enjoying “no credibility … [and for] being filled with lies, hearsay and propaganda” (p. 134). Alternatively, Zayyan and Carter () find citizen journalism operating outside the structures of officialdom as making critical “political interventions in their own right” (p. 93) and playing a central role “… in widening public debates on the Middle East conflict and in highlighting the ways in which such reporting bears witness to its human consequences” (p. 86).…”
Section: Contextualizing Hamas‐led Media Culturementioning
confidence: 99%